“Enhancing VAP Prevention: Impact of a Care Bundle Training Module for ICU Nurses” - Ms. Lata; Ms. Deepa Mukherjee; Prashant Sharma; Mr. Naveen (The Bioscan, 2025)
Ventilator-Associated Pneumonia (VAP) remains one of the most preventable yet life-threatening infections among mechanically ventilated patients in Intensive Care Units (ICUs). Its impact—prolonged hospitalization, increased treatment costs, and heightened mortality—highlights the crucial role of competent nursing practices in prevention. This study was designed to evaluate the effectiveness of a structured teaching module in enhancing ICU nurses’ knowledge and clinical practices related to VAP prevention in a selected hospital in Gurugram. Using a quasi-experimental one-group pre-test post-test design, 60 ICU nurses were selected through purposive sampling. Their baseline knowledge and practices were assessed using a structured questionnaire and observational checklist. A three-day evidence-based educational intervention—featuring interactive lectures, group discussions, and hands-on demonstrations—was implemented to strengthen their understanding and application of VAP care bundle practices. Findings demonstrated a considerable rise in knowledge levels among the experimental group (adequate knowledge increased from 3.3% to 33.3%) along with a statistically significant improvement in practice performance (p = 0.005). Although the overall knowledge gain was not statistically significant (p = 0.066), the practical enhancement underscores the value of skill-based learning. In contrast, the control group showed a significant decline in knowledge (p = 0.000) despite an improvement in practice (p = 0.000). Age and workload type were significantly associated with post-test knowledge, while workload type influenced practice in the experimental group; patient load was the only significant factor affecting knowledge in the control group. The study concludes that structured, evidence-based teaching modules substantially improve ICU nurses’ competence in preventing VAP. Integrating regular training on VAP care bundles into hospital education systems can bridge the knowledge–practice gap and contribute to safer, more effective patient care.